專題式學習運用在國小環境教育課程之實踐歷程與成效 - 姜緯珊(Wei-Shan Chiang); 詹惠雪(Hui-Hsueh Chan) (Shizi Peiyu Yu Jiaoshi Zhuanye Fazhan Qikan, 2024)
This study investigated the application of Project-based Learning in the fifth-grade environmental education curriculum of elementary schools, with the aim of understanding its effectiveness and impact on students' learning as measured against a self-developed Environmental Education Literacy Scale. From October to December 2023, two cycles of 20 lessons were conducted using Big6 skills as the teaching steps. A comprehensive analysis was performed using various data sources, including the Environmental Literacy Scale, the Big6 Skills Assessment Scale, teachers' reflective notes, classroom observation records, interview records, and Big6 worksheets. The findings showed that 1. teacher first led students to complete the Project-Based Environmental Education Curriculum and then gradually released them to explore on their own, but there was still a need for continuous deepening of learning; 2. Big6 skills needed to be combined with multiple strategies to help students complete the project; 3. the Project-Based En